2017
DOI: 10.4314/ahs.v17i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular screening of antibiotic-resistant determinants among multidrug-resistant clinical isolates of <i>Proteus mirabilis</i> from SouthWest Nigeria

Abstract: Background: Globally, and particularly in developing countries, the menace of anti-microbial resistance is an accelerating problem. In Nigeria, increase in bacterial resistance has been phenotypically established but due to high cost, few molecular studies have been reported. Objectives: This study screened for presence of transferable resistance genes and mobile genetic elements (MGEs) such as integron among multi-drug resistant (MDR) P. mirabilis. Methods: A total of 108 P. mirabilis strains collected from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
5
18
0
Order By: Relevance
“…On the contrary, the highest sensitivity was against ceftriaxone (96.8%), norfloxacin (82.5%), gentamicin (71.4%), and ciprofloxacin (69.8%). Similar results have been reported for P. mirabilis from Nigeria, where isolates' resistance rates to ciprofloxacin, nalidixic acid, sulfamethoxazole, and gentamicin were 13.9%, 53.7%, 74.1%, and 26.9%, respectively [21]. In Czech Republic, the isolates had a resistance rate of ciprofloxacin (35.2%), sulfamethoxazole (39.0%), ampicillin (38.5%), and gentamicin (25.4%), which are different form findings of the present study [22].…”
Section: Discussionsupporting
confidence: 85%
“…On the contrary, the highest sensitivity was against ceftriaxone (96.8%), norfloxacin (82.5%), gentamicin (71.4%), and ciprofloxacin (69.8%). Similar results have been reported for P. mirabilis from Nigeria, where isolates' resistance rates to ciprofloxacin, nalidixic acid, sulfamethoxazole, and gentamicin were 13.9%, 53.7%, 74.1%, and 26.9%, respectively [21]. In Czech Republic, the isolates had a resistance rate of ciprofloxacin (35.2%), sulfamethoxazole (39.0%), ampicillin (38.5%), and gentamicin (25.4%), which are different form findings of the present study [22].…”
Section: Discussionsupporting
confidence: 85%
“…47 In another study in Nigeria, aac(6ʹ)-Ib-cr and qnrA genes were detected in 3 (5%) and 22 (36.7%) of the MDR P. mirabilis isolates, respectively, while none was positive for qepA. 48 According to the PFGE analysis, most of the isolates were clonally unrelated, and only four pulsotypes with more than one isolate were defined. Pulsotype 4 was related to 2 identical isolates (100% similarity) from different wards at the same hospital that maybe alarming for the dissemination of these isolates in different wards in a hospital.…”
Section: Discussionmentioning
confidence: 98%
“…In 2017, this rate was significantly higher in Nigeria where qnrA and aac(6 )-Ib-cr were detected in, respectively, 36.7 and 5% of the 108 multidrug resistant P. mirabilis tested. These genes were most often carried associated with β-lactamase genes (bla TEM or bla CTX−M ) on class 1 and class 2 integrons (Alabi et al, 2017). It was observed that the qnrB10 and aac(6 )-Ib-cr genes were significantly associated with the ESBL genes whereas this is not the case for the qnrB19 nor qnrD (Albornoz et al, 2014).…”
Section: Resistance To Quinolones In Proteus Sppmentioning
confidence: 96%